Bifidobacteria define gut microbiome profiles of golden lion tamarin (Leontopithecus rosalia) and marmoset (Callithrix sp.) metagenomic shotgun pools - Joanna Malukiewicz; Mirela D’arc; Cecilia A. Dias; Reed A. Cartwright; Adriana D. Grativol; Silvia Bahadian Moreira; Antonizete R. Souza; Maria Clotilde Henriques Tavares; Alcides Pissinatti; Carlos R. Ruiz-Miranda; André F. A. Santos (Scientific Reports, 2023)
Abstract Gut microbiome disruptions may lead to adverse effects on wildlife fitness and viability, thus maintaining host microbiota biodiversity needs to become an integral part of wildlife conservation. The highly-endangered callitrichid golden lion tamarin (GLT-Leontopithecus rosalia) is a rare conservation success, but allochthonous callitrichid marmosets (Callithrix) serve as principle ecological GLT threats. However, incorporation of microbiome approaches to GLT conservation is impeded by limited gut microbiome studies of Brazilian primates. Here, we carried out analysis of gut metagenomic pools from 114 individuals of wild and captive GLTs and marmosets. More specifically, we analyzed the bacterial component of ultra filtered samples originally collected as part of a virome profiling study. The major findings of this study are consistent with previous studies in showing that Bifidobacterium, a bacterial species important for the metabolism of tree gums consumed by callitrichids, is an important component of the callitrichid gut microbiome - although GTLs and marmosets were enriched for different species of Bifidobacterium. Additionally, the composition of GLT and marmoset gut microbiota is sensitive to host environmental factors. Overall, our data expand baseline gut microbiome data for callitrichids to allow for the development of new tools to improve their management and conservation.